New laws, road wars, courtesy and animosity: Cycling safety in Queensland newspapers. (November 2016) - English, Peter; Salmon, Paul
Highlights: The media portrayal of cyclists was overwhelmingly negative. There was a lack of understanding from readers about the new cycling laws. The "road wars" issue highlights the challenges road users still face in the media. The role of the road environment in road crash causation was not apparent. The style of media coverage of cyclists could dissuade riders from participating. Abstract: The media play an important role in road safety and have a significant influence on road user behaviours. This is achieved through educating road users and communicating safety issues. The issue of cycling safety was again prominent in 2014 when the Queensland Government in Australia trialled new laws to improve cycling conditions. In Australia, the relationship between cyclists and motorists has been described as "road wars", and a one metre passing law was introduced to reduce cycling fatalities and improve road sharing. The aim of this study was to examine the media portrayal of cyclists and cycling following the introduction of the changes. A content analysis of 12 Queensland daily newspapers was undertaken to investigate topics in relation to the new laws, cycling safety, road wars, road factors, accidents, and blame. Data was collected between April, 2014 and January, 2015, with a sample of 467 story items. Analysis of the stories showed a highly negative portrayal of the new laws and cyclists, particularly through user-generated content. The implications for road safety and future road safety-related media activities are discussed.